PERANAN KELUARGA MATRILINEAL MINANGKABAU TERHADAP KESEJAHTERAAN PEREMPUAN LANJUT USIA - Lucky Zamzami (Puslitbangkesos Kementerian Sosial RI, 2010)
Increased of elderly people in every year have to follow by a good service, either by family and alsoÂ govemment in effort improve their social prosperity. The elderly people placed respectable on course and made happy in family life and young generation suggested in honour and responsible of prosperity of the older family, especially parent itself Thereby, family is the right means to serve the elderly people, especially elder women in family, because family has obligation of moral for remain takecare and serve the elderly people in family.This research explore such problems related with elderly women condition in Minangkabau society in the past and now, acces and pattem of social responsibilihJ to elderly women existence which not affected by values of institutions of elderly people place (panti jompo), so the elderly women existence always get a social security by family in Minangkabau. The research employs qualitative approach by doing a participant method. The data is collected by interviewing the informants using a list of questions. The informants are identified using snow ball technique.The findings show role of matrilineal family in West Sumatra (Minangkabau) to the elderly women existence is holding fully responsibility in giving a good service, so that the elderly women don 't be unemployed and feel happy with condition of family. Besides that, family felt obliged to give freedom inÂ improve their prosperity by following social activities. They have social organization is Mawar group, which formed by sub-district goverment. Existence of social organization in elderly women activities was impact to their health and improve for their skill.